A Selective Membrane Electrode for Iodide Ion based on New Ionophore and its Application to Pharmaceutical Samples - Omid Hossieni1, Sayed Aboalfazl Maashi2, Narges Chamkouri1* Zolfaghar Sabati2, Pardis Nourbakhsh2, M (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background and Objectives: On the basis of newly synthesized i.e. imidazolidine-2tion (IMT), highly selective poly vinyl chloride (PVC) membrane electrode was utilized as a carrier for iodide selective electrode via the incorporation of membrane ingredients within the graphite electrode surface. Method: The impact of different factors consisting of the pH, membrane arrangement and likely intervening anions were examined on the electrode’s response characteristics. The created sensor displayed Nernstian responses to iodide across a concentration of 1× 10-6 to 0.1 M with slopes of 57.8± 0.7 mV per iodide concentration decade and 7 × 10-7M detection limit, across a pH range of 3.0-10.5. Results: The sensor response time was 6 seconds and may be used for a minimum of 2 months with no significant divergence at potential responses. Conclusion: The electrode was implemented with success to determine iodide within synthetic pharmaceutical samples as well as using as an indicator electrode for precipitation titration.